An Architecture of 2-Dimensional 4-Dot 2-Electron QCA Full Adder and Subtractor with Energy Dissipation Study - Md. Abdullah-Al-Shafi; Ali Newaz Bahar (Active and Passive Electronic Components)
Quantum-dot cellular automata (QCA) is the beginning of novel technology and is capable of an appropriate substitute for orthodox semiconductor transistor technology in the nanoscale extent. A competent adder and subtractor circuit can perform a substantial function in devising arithmetic circuits. The future age of digital techniques will exercise QCA as preferred nanotechnology. The QCA computational procedures will be simplified with an effective full adder and subtractor circuit. The deficiencies of variations and assembly still endure as a setback in QCA based outlines, and being capricious and inclined to error is the limitation of these circuits. In this study, a new full adder and subtractor design using unique 3-input XOR gate with cells redundancy is proposed. This designs can be utilized to form different expedient QCA layouts. The structures are formed in a single layer deprived of cross-wiring. Besides, this study is directed to the analysis of the functionality and energy depletion possessions of the outlined full adder and subtractor circuits. For the first time, QCADesigner-Energy (QD-E) version 2.0.3 tool is utilized to find the overall depleted energy. The attained effects with QCADesigner have verified that the outlined design has enhanced functioning in terms of intricacy, extent, and latency in contrast to the earlier designs. Moreover, the redundant form of full adder and subtractor has uncomplicated and robust arrangement competing typical styles.